Role of Early Intervention in Improving the Clinical Outcome of Acute Pancreatitis by Image Guided Percutaneous Catheter Drainage of Pancreatic Collections - Sudha, Chittoor Ramya; Samireddypalle, Yugandhar; Reddy, Umamaheswara V; Dembla, Sagar; Gurudutt P. Varty; Dhawan, Ankita Sanjeev; Amitha K S Vikrama (Asian Journal of Medical Radiological Research, 2020)
Background: To assess the role of image guided percutaneous drainage of acute pancreatic collections in influencing the clinical outcome of patients. Subjects and Methods: This is a prospective study done in the department of intervention radiology, Narayana medical college. About 20 cases have been performed in our institution from January 2019 to December 2019. All these drainage procedures have been done under CT guidance. All these cases were strictly followed during their hospital course. Clinical success has been defined as control of sepsis and prevention of MODS without the requirement of surgical debridement. Results: Out of twenty cases, which we intervened, there was an improvement in clinical outcome in fourteen cases with the prevention of septic shock and multiorgan failure. Three cases were critically ill at the time of admission and succumbed to MODS (Multiple organ dysfunction syndrome). The other three cases required additional surgical intervention-debridement. In which, there was increased morbidity with delayed recovery in two cases, and one case developed MODS and expired. Conclusion: Image guided Percutaneous catheter drainage is a safe and effective technique to drain pancreatic collections. Adequate knowledge regarding the interpretation of imaging findings, time to intervene, adequate expertise for performing the procedure, close follow up with regular clinical assessment is vital in the management of patients in acute pancreatitis. Early and aggressive intervention helps reduce the morbidity and mortality by preventing the evolution of MODS.